VD_FINDINFO Arrêt / 2025 / 164 vom 10. April 2025 - VD Tribunal cantonal (2025)
AIASSURANCE, ÉVALUATION DE L'INVALIDITÉ, EXPERTISE PLURIDISCIPLINAIRE, FIBROMYALGIE, RENTE ÉCHELONNÉE | 28 LAI, 29 LAI, 4 al. 1 LAI, 16 LPGA, 17 al. 1 LPGA, 6 LPGA, 7 LPGA, 8 al. 1 LPGA, 88a al. 1 RAI